John Chrysostom and Severian of Gabala : homilists, exegetes and theologians - Leemans, Johan, 1965-; Roskam, Geert; Segers, Josien (Orientalia Lovaniensia analecta, 2019)
"The homiletic corpora of John Chrysostom and Severian of Gabala are major yet understudied sources documenting late antique Christianity. With their sermons on Genesis as focal point, the studies in this volume contribute in many ways to advancing the state of the art. S. Voicu offers a complete survey of research on Severian, including a check-list of his authentic works. S. Kim, J. Oosterhuis-den Otter and L. Sels-S. Van Pee contribute to text-critical research on Severian, P. Augustin to that of Chrysostom. Read together, the articles by R. Bishop, W. Mayer and P. Van Nuffelen offer fresh perspectives on the tensions between Chrysostom and Severian. H. Buchinger discusses what can be gleaned from their sermons about the liturgy at Constantinople. K. Papadopoulos engages with Severian's biblical exegesis while S. Miller and P. Molinié analyse the content of some of the sermons. As a whole, the volume offers fresh insights in the writings and thought of two important late antique Christian bishops and theologians and opens up many avenues for further research."--